Kosakata Patriarki dalam Buku Teks Bahasa Indonesia Siswa (Tinjauan Teorisasi Patriarki Sylvia Walby) - Suriadi, Suriadi; Baharman, Baharman (Nuances of Indonesian Language, 2024)
This research aims to describe the vocabulary that represents the structure of patriarchal ideology in texts found in student textbooks. This is a qualitative descriptive research that critically analyzes the hidden meanings behind texts typically considered natural, using Sylvia Walby's theory of patriarchy. The instrument used in this research is the researcher (human instrument). The data for this research are the content presented in textbooks, with the data source is the Indonesian language textbooks for Grade VII of the 2013 Curriculum published by the Ministry of Education and Culture. The data presentation method used in this research was the listening method that  using listening free speaking and note-taking techniques. The results of data analysis indicate that there is a significant amount of vocabulary representing the structure of patriarchal ideology. The vocabulary found predominantly illustrates the structure of patriarchal relations in cultural institutions, characterized by the masculinity of men and the femininity of women.